Range of neurologic disorders in patients with celiac disease - Zelnik, Nathanel; Pacht, Avi; Obeid, Raid; Lerner, Aaron (Pediatrics (Evanston), 2004)
During the past 2 decades, celiac disease (CD) has been recognized as a multisystem autoimmune disorder. A growing body of distinct neurologic conditions such as cerebellar ataxia, epilepsy, myoclonic ataxia, chronic neuropathies, and dementia have been reported, mainly in middle-aged adults. There still are insufficient data on the association of CD with various neurologic disorders in children, adolescents, and young adults, including more common and "soft" neurologic conditions, such as headache, learning disorders, attention-deficit/hyperactivity disorder (ADHD), and tic disorders. The aim of the present study is to look for a broader spectrum of neurologic disorders in CD patients, most of them children or young adults. Patients with CD were asked to fill in a questionnaire regarding the presence of neurologic disorders or symptoms. Their medical charts were reviewed, and those who were reported as having neurologic manifestations underwent neurologic examination and brain imaging or electroencephalogram if required. Their neurologic data were compared with that of a control group matched for age and gender. Patients with CD were more prone to develop neurologic disorders (51.4%) in comparison with control subjects (19.9%). These disorders include hypotonia, developmental delay, learning disorders and ADHD, headache, and cerebellar ataxia. Epileptic disorders were only marginally more common in CD. In contrast, no difference was found in the prevalence of tic disorders in both groups. Therapeutic benefit, with gluten-free diet, was demonstrated only in patients with transient infantile hypotonia and migraine headache. This study suggests that the variability of neurologic disorders that occur in CD is broader than previously reported and includes "softer" and more common neurologic disorders, such as chronic headache, developmental delay, hypotonia, and learning disorders or ADHD. Future longitudinal prospective studies might better define the full range of these neurologic disorders and their clinical response to a gluten-free diet.